On deferred statistical convergence of order β of sequences of fuzzy numbers - Et, Mikail; Erol, Yüksel (Journal of intelligent & fuzzy systems, 2018)
The main purpose of this paper is to introduce and examine the concepts of deferred statistical convergence of order β and strong r-deferred Cesáro summability of order β for sequences of fuzzy numbers and give some relations between deferred statistical convergence sequences of order β and strongly r-deferred Cesáro summable sequences of order β, where β ∈ (0, 1] and p ∈ ℝ + . Mathematics Subject Classification: 40A05, 40C05, 46A45, 03E72.